Evaluation of Library Services for People with Visual Disability in Jordan in Light of International Standards - Al-Zboon, Eman; Al-Hadidi, Muna (Jordan Journal of Educational Sciences, 2013)
The purpose of this study was to evaluate the current status of the library services provided to people with visual disability in Jordan for the year (2012) and compare them to international practices and standards. The study sample consisted of (32) public and private libraries in public and private universities and major public libraries. A scale of international standards for the library services provided to people with visual disability was developed. The scale consisted of six key standards covering (55) indicators and acceptable connotations of validity and reliability for the purposes of this study were derived, before being applied to study sample, and then data were analyzed. The results of the study indicated that the availability of international standards for services for people with visual disability was very low level as a total score (with a mean of = 0.1329) and in the domains of: Services of library patrons (with a mean of 0.1055), library building (with a mean of 0.304), human resources (with a mean of 0.0508), public relations (with a mean of 0.1000), sources of information (with a mean of 0.1250), tools and equipment and new technology (with a mean of 0.0889). In the domains of the library building, the level was low (with a mean of 0.304)